Effects of plyometrics and Pilates training on physical fitness skills of male karate athletes - Pal, S.; Yadav, J.; Sindhu, B.; Laöra, S. (Journal of University of Shanghai for Science and Technology, 2020)
Background: There has been an increase in the participation in Karate in the past decades and now it is practiced and played across the worldwide. The success of the karate player mainly depends on the physical fitness qualities like agility, power and speed. Improvement in these physical variables depends upon the type of exercise training used by the athletes. In the Indian context there is lack of literature that supporting the use of Pilates and Plyometric training programme in training of Karate players. Therefore, to achieve success in the sport best training method should be chosen by athletes or coaches. Purpose: To compare the effectiveness of two training programs Pilates and Plyometric on sports specific physical skills of aspiring National level male Karate players. Materials and Methods: The design of this study was experimental and sampling technique was simple random sampling. This study is conducted on a sample size of 40 in each group Experimental group A (Plyometrics, N=40), Experimental group B (Pilates, N=40) and Control group C (N= 40). The national level male karate players (age 18 to 24 Years) with playing experience of 5 years were included. Recreational players, players with recent injury in past 6 months, any musculoskeletal and neurological problem, player addicted to any drug or alcohol were excluded. The plyometric and pilates training were carried out in experimental groups for three days per week for 8 weeks and no training method implemented in the control group. Three reading were recorded, at the baseline, at the 4th week and at the 8th week. Agility, power and speed were the outcome measurements. All analysis was done using the SPSS version 2.0. Descriptive statistics were reported as mean, Standard Deviation (SD) and ANOVA were calculated. The significance level was set at p< 0.05. Results: When the pre and post test values of the experimental groups have been compared at the 4th week and 8th week of the study, the significant improvement (p< 0.005) was found in the agility, power and 40 yard sprint test of the plyometric group (group A). Both the training methods have showed improvements in the physical fitness skills. Conclusion: The findings of the present study revealed that plyometrics and pilates both can improve physical fitness skills of karate players but the plyometric training method had more positive and better effects on agility, power and speed on karate athletes than pilates group in the view of sports performance.